2017
DOI: 10.1002/adfm.201770253
|View full text |Cite
|
Sign up to set email alerts
|

LEDs: High‐Efficiency and Stable Quantum Dot Light‐Emitting Diodes Enabled by a Solution‐Processed Metal‐Doped Nickel Oxide Hole Injection Interfacial Layer (Adv. Funct. Mater. 42/2017)

Abstract: A Cu‐doped, NiO‐based quantum dot light‐emitting diode (QLED) reported by Xuyong Yang and co‐workers in article number https://doi.org/10.1002/adfm.201704278 exhibits a significant operating lifetime enhancement compared with organic PEDOT:PSS‐based QLEDs. Relying on an inorganic hole transport layer, the device's quantum dots retain their brightness for an extended time period. This is in contrast to light from a PEDOT:PSS‐based QLED shown in the upper‐left corner of the image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…An ≈4 nm redshift for the electroluminescence (EL) emission peak as compared to the PLEM peak is observed (Figure 4d), which is attributed to inner NCs interaction and Stark effect induced by the external electric field . The current density–voltage ( J – V ), luminance–voltage ( L – V ), current efficiency–luminance ( C – L ), and EQE–luminance (EQE–L) characteristics are shown in Figure 4e,f.…”
mentioning
confidence: 94%
“…An ≈4 nm redshift for the electroluminescence (EL) emission peak as compared to the PLEM peak is observed (Figure 4d), which is attributed to inner NCs interaction and Stark effect induced by the external electric field . The current density–voltage ( J – V ), luminance–voltage ( L – V ), current efficiency–luminance ( C – L ), and EQE–luminance (EQE–L) characteristics are shown in Figure 4e,f.…”
mentioning
confidence: 94%
“…It is of interest to exploit the excellent stability of oxide materials to increase the operational lifetime of QLEDs. For this purpose, high‐performance solution‐processed oxide HILs have been actively pursued in the QLED field . Recently, Yang and co‐workers introduced solution‐processed Cu:NiO HILs in QLEDs, leading to devices with a maximum external quantum efficiency (EQE) of 10.5% and a half operational lifetime of 87 h at an initial brightness of 5000 cd m −2 .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, high‐performance solution‐processed oxide HILs have been actively pursued in the QLED field . Recently, Yang and co‐workers introduced solution‐processed Cu:NiO HILs in QLEDs, leading to devices with a maximum external quantum efficiency (EQE) of 10.5% and a half operational lifetime of 87 h at an initial brightness of 5000 cd m −2 . Sun et al reported a flexible QLED using solution‐processed NiO as HILs, demonstrating a maximum current efficiency of 45.8 cd A −1 , a maximum EQE of 10.9%, and a half operational lifetime of 49.3 h at an initial brightness of 7182 cd m −2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations